LD

x-(17-x)=x-7

trinh bày cách giải luôn nha

 

H24
31 tháng 12 2015 lúc 10:20

Ta có:
x−(17−x)=x−7
\(\Rightarrow\) x−17+x=x−7
\(\Rightarrow\) x=−7+17=10

Bình luận (0)
MH
31 tháng 12 2015 lúc 10:21

x-(17-x)=x-7

=> x-17+x=x-7

=> 2x-17=x-7

=> 2x-x=-7+17

=> x=10

Bình luận (0)
TT
31 tháng 12 2015 lúc 10:23

    x-(17-x)=x-7

=>x-17+x=x-7

=>x-10+x=x

=>x+x-10=x

=>x-10=x-x

=>x=10

Bình luận (0)
LV
6 tháng 3 2016 lúc 17:44

x-(17-x)=x-7

x-17+x=x-7

2x-17=x-7

2x+x=-7+17

2x+x=10

x=10

Bình luận (0)